SOSIALISASI PEMANFAATAN TEKNOLOGI UNTUK PENGOLAHAN LIMBAH SAMPAH ORGANIK MASYARAKAT MENJADI PUPUK KOMPOS DI DESA HILISONDREKHA - Gea, Karunia; Leonardus Historis Manao; Firdaus Laia (Universitas Nias Raya, 2024)
The aim of this service activity is to provide understanding to the community, especially in Hilisondrekha Village, South Nias Regency, about how to make compost fertilizer from organic waste and the technology used in processing it. The method used in this activity is the lecture method in the form of socialization with participants consisting of the Hilisondrekha Village community. This activity was carried out at the Hilisondrekha Village Hall, South Nias Regency on Friday 17 May 2024. The results obtained from this service in Hilisondrekha Village were that the community was able to process organic waste into organic fertilizer. Activities to utilize technology to process community organic waste have been carried out well. One of the most important factors in processing organic waste into compost is that it can preserve the village environment and is beneficial for community plants. The conclusion of this service activity is that people can make their own fertilizer and sort organic waste from non-organic waste.